Legal tech in legal service: challenging the traditional legal landscape in Malaysia - Abd. Jalil, Juriah; Mohd. Sheriff, Shukriah (IIUM Press, 2020)
Digital technologies are now extending its function to the legal profession. But the existence of these technologies otherwise known as legal technology (legal tech) or law tech is challenging the traditional legal profession. The nature of legal practice regulation in Malaysia and the United Kingdom (UK) permits only lawyers and authorised persons as legal service providers. As a result, the legal tech or law tech companies although able to facilitate the service in the legal profession are met with resistance and/or indifference. Should the traditional legal profession fear the invasion of this legal tech? This article aims to analyse the situation in Malaysia and the UK. It examines the impact of technology on legal service and legal profession in Malaysia and in the UK. The article also highlights the implication of this legal technology on the laws governing the legal profession in Malaysia. Through analyses of key Malaysian cases, the study finds that the Bar Council has the power to halt the operation of legal tech companies in providing any legal service in this country.As a result, the Bar has been criticised for being a hindrance to the development of legal tech in Malaysia. In contrast, the UK and the United States of America (US) have been very receptive to legal technology despite the exclusivity in the legal profession.